Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1002/1873-3468.12264
|View full text |Cite
|
Sign up to set email alerts
|

Species differences in unlocking B‐side electron transfer in bacterial reaction centers

Abstract: The structure of the bacterial photosynthetic reaction center (RC) reveals symmetry-related electron transfer (ET) pathways, but only one path is used in native RCs. Analogous mutations have been made in two Rhodobacter (R.) species. A glutamic acid at position 133 in the M subunit increases transmembrane charge separation via the naturally inactive (B-side) path through impacts on primary ET in mutant R. sphaeroides RCs. Prior work showed that the analogous substitution in the R. capsulatus RC also increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 65 publications
1
29
1
Order By: Relevance
“…2A) and close to the position of P + B A − in WT (18,19). We have previously shown that these 3 mutations in R. sphaeroides RCs result in ∼20% yield of P* → P + H B − and that additionally replacing ThrM133 with Glu increases the P + H B − yield to ∼60% (17). These 4 mutations are the core of 2 RC backgrounds used here, denoted bg1 and bg2.…”
mentioning
confidence: 71%
See 3 more Smart Citations
“…2A) and close to the position of P + B A − in WT (18,19). We have previously shown that these 3 mutations in R. sphaeroides RCs result in ∼20% yield of P* → P + H B − and that additionally replacing ThrM133 with Glu increases the P + H B − yield to ∼60% (17). These 4 mutations are the core of 2 RC backgrounds used here, denoted bg1 and bg2.…”
mentioning
confidence: 71%
“…On the B side, the residue that is related by C 2 symmetry to GluL104 is ThrM133, which is changed to Glu here in bg1, bg2, Arg-bg1, and Arg-bg2 RCs. Glu substituted at M133 is also thought to be neutral and make a hydrogen bond to H B because this substitution is shown in prior work (17,(31)(32)(33)(34) to red shift the Q x bands of H B by ∼7 nm (SI Appendix, Table S2). We find here that the presence of ArgL185 results in a blue shift of the Q x bands of H B by ∼7 nm in Arg-bg1 and Arg-bg2 RCs compared to bg1 and bg2 RCs (SI Appendix, Figs.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…1B) (20)(21)(22) but it is difficult to determine these energetics either experimentally or theoretically (1,23). Contributions of individual symmetry-breaking amino acid have been thoroughly studied (1,15,(24)(25)(26)(27)(28) and while the importance of certain amino acids has been ascertained, the roles of local protein-chromophore interactions are not always fully understood (8,24,25). One highly examined residue has been the tyrosine at site M210 (RC residue numbers are preceded by the protein subunit designation: H, L, or M) because it is a clear deviation in symmetry between A-and B-branches (Fig.…”
Section: Introductionmentioning
confidence: 99%